Effect of dihydrotestosterone, 17-β-estrogen, genistein and equol on remodeling and morphology of bone in osteoporotic male rats during bone healing - Philipp Kauffmann (Bone Reports, 2020)
Introduction: The aim of this study was to investigate the effect of dihydrotestosterone (DHT), 17-β-estrogen (E2), genistein (GEN) and equol (EQ) on bone remodeling and bone morphology during healing of osteoporotic male rat tibiae. Materials and methods: 180 Sprague-Dawley male rats were divided in 5 groups of 36 animals. After orchidectomy (ORX) and development of osteoporosis, trepanation of the tibia was performed. Until the time of trepanation all groups received soya free food (SF), then food change occurred and treatment started. At day 95, 102 and 151, samples were taken and histomorphometry was performed to analyze changes in bone structure under treatment. At day 33 and 70 all animals received calcein respective alizarin for polychrome bone labeling. Results: The cortical bone was particularly affected. Treatment with DHT and E2 led to a significant long-term expansion of the thickness of the diaphyseal cortical bone, while the phytoestrogens EQ and GEN only had a positive short-term effect in this area. Only E2 preserved the trabecular bone for a limited time. In all groups, periosteal and endosteal bone areas showed the highest bone formation activity. The osteoporotic male injured bone shows a shift in mineral apposition rate (MAR) from periosteal to endosteal bone in the SF, DHT and E2 groups but not in the GEN and EQ phytohormones groups. An MAR decrease in trabecular bone formation was observed at day 70 in all groups except the E2 group. Conclusion: We conclude from our results that healing of cortical bone defects in a rat model of male osteoporosis are mainly influenced by the estrogen pathway. Nevertheless, effects via purely androgenic mechanisms can also be demonstrated. The role of a phytohormone therapy is only marginal and if only useful for a short-term supportive approach. The role of the periosteal to endosteal shift during male osteoporotic bone healing needs to be further examined.